2021
DOI: 10.1002/advs.202100370
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Arginine–Glycine–Aspartate‐Decorated Lipid Nanoparticle Targeting toward Inflammatory Lesions Involves Hitchhiking with Phagocytes

Abstract: Active-targeting nanomedicine formulations have an intricate in vivo behavior. Nanomedicines developed to target endothelial v 3 -integrin are recently demonstrated to display extensive uptake by circulating phagocytes. These phagocytes show inherent tumor-homing capacities and therefore are capable of actively delivering the endocytosed nanomaterial in lesions. Here, the targeting kinetics and mechanisms of cyclic arginine-glycine-aspartate (cRGD)-decorated lipid nanoparticles (NPs) toward activated vasculatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 57 publications
(77 reference statements)
0
12
0
Order By: Relevance
“…In addition, it is important to state that CCPM is a formulation with negligible formation of protein corona [57], therefore low decoration densities might be suitable for maintaining this desirable feature for prolonged circulation and efficient tumor targeting. In addition, we [13,18,31] and others [23,46,53,58] have observed that low decoration densities (i.e., 1 mol% or lower) are sufficient for significantly altering the in vivo behavior between ligand-decorated and non-decorated analogs. Of note, and considering our goal to evaluate this drug delivery system in vivo, the used nanoformulation has already undergone extensive investigation regarding shelf stability [59], and serum stability and protein binding examined via asymmetrical flow field-flow fractionation [57].…”
Section: Identifying the Optimal Crgd Decoration Density For Follow-u...mentioning
confidence: 68%
See 1 more Smart Citation
“…In addition, it is important to state that CCPM is a formulation with negligible formation of protein corona [57], therefore low decoration densities might be suitable for maintaining this desirable feature for prolonged circulation and efficient tumor targeting. In addition, we [13,18,31] and others [23,46,53,58] have observed that low decoration densities (i.e., 1 mol% or lower) are sufficient for significantly altering the in vivo behavior between ligand-decorated and non-decorated analogs. Of note, and considering our goal to evaluate this drug delivery system in vivo, the used nanoformulation has already undergone extensive investigation regarding shelf stability [59], and serum stability and protein binding examined via asymmetrical flow field-flow fractionation [57].…”
Section: Identifying the Optimal Crgd Decoration Density For Follow-u...mentioning
confidence: 68%
“…In this study, we decorated CCPM with an arginineglycine-aspartic acid peptide (i.e., RGD; note that the cyclic RGDfK pentapeptide was used), as it is one of the most well-known active targeting ligands tested both preclinically and clinically [22][23][24][25][26][27][28] and holds promise for targeting not only cancer cells but also activated endothelial cells [29], stromal cells [30], and immune cells [31]. In addition, cRGD has been shown to increase the accumulation of nanomedicines in tumors by promoting transcytosis [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is important to state that CCPM is a formulation with negligible formation of protein corona [55], therefore low decoration densities might be suitable for maintaining this desirable feature for prolonged circulation and e cient tumour targeting. In addition, we [13,18,31] and others [23,44,51,56] have observed that low decoration densities (i.e., 1 mol% or lower) are su cient for signi cantly altering the in vivo behavior between ligand-decorated and non-decorated analogues.…”
Section: Identifying the Optimal Crgd Decoration Density For Follow-u...mentioning
confidence: 88%
“…In this study, we decorated CCPM with an arginine-glycine-aspartic acid peptide (i.e., RGD; note that the cyclic RGDfK pentapeptide was used), as it is one of the most well-known active targeting ligands tested both preclinically and clinically [22][23][24][25][26][27][28], and holds promise for targeting not only cancer cells, but also activated endothelial cells [29], stromal cells [30] and immune cells [31]. By producing CCPM with three different decoration densities of cRGD (0, 1, 3.6 and 5 mol%) and a control composition without cRGD decoration, we aimed at assessing the biological activity of the ligand when anchored on the nanoformulation, as well as at examining whether higher decoration densities are meaningful for improving target binding and internalization.…”
Section: Introductionmentioning
confidence: 99%
“…αvβ3 is not only expressed on activated endothelial cells but also on many tumor cells and on macrophages [ 24 ]. It was shown recently that homing of cRGD-decorated nanocarriers to tumor vasculature may also occur by action of phagocytes, substantiating that targeting angiogenic sites with cRGD-containing constructs may involve other mechanisms than straightforward binding to endothelial αvβ3-integrin [ 25 ]. Moreover, there are selective ligands for αvβ3-integrin which do not rely on the RGD motif [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%